Vocabulary Growth in Lexical Categories Between Ages 13 and 24 Months as a Function of the Child’s Sex, Child, and Family Factors - Nylund, Annette; Ursin, Piia af; Korpilahti, Pirjo; Rautakoski, Pirkko (Frontiers in Communication, 2021)
We examined the vocabulary growth of lexical categories in 719 children (age 13 to 24 months) as part of a longitudinal cohort study (the STEPS Study) and found a discrepancy in how these categories were affected depending on the child´s sex. In girls, attending day care at 24 months of age predicted a positive vocabulary growth in the lexical categories sound effects, nouns, people, and games and routines, compared to girls staying at home. Firstborn girls had a greater vocabulary growth in descriptive and function words, in contrast to those born later. A boy attending day care at age 24 months was likely to have greater growth in sound effects and animal sounds, compared to boys not in day care. A family history of late onset of speech predicted less vocabulary growth in all lexical categories in boys, except for sound effects and animal sounds. Early vocabulary is of importance for later language and literacy development. Vocabulary is not an impenetrable entirety but consists of various types of words (lexical categories) developing at different tempos as they contribute to the developing language. Factors influencing early vocabulary development in boys and girls have been painstakingly studied, but fewer have examined these factors across lexical categories, let alone whether they have an equal effect in both sexes. More knowledge of what affects the variation in early vocabulary in boys and girls is needed for clinical practice and preventive purposes. Vocabulary was measured with the Finnish version of the MacArthur Communicative Development Inventory. The effect of child and family factors on vocabulary growth in various lexical categories was analyzed separately for boys and girls using structural equational modelling. The results of the present study indicate that vocabulary development in the lexical categories is affected differently by child and parental factors in girls and boys as early as the second year of life, which gives new insights into the factors that need consideration in clinical practice and preventive work.